Employer Branding Meets Digital Capability: An Empirical Study on Employee Engagement and Turnover Intention in SMEs - Mila Sartika; Vincent Didiek Wiet Aryanto; Kusni Ingsih (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to analyze the influence of employer branding and digital capability on turnover intention, with employee engagement serving as a mediating variable, in Small and Medium Enterprises (SMEs) in Central Java Province. The research design uses a quantitative approach with an explanatory research method. The research sample consists of 205 SMEs employees selected using purposive sampling techniques with criteria of a minimum of six months of service and active use of digital technology in their work. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that employer branding has a positive effect on employee engagement and a negative effect on turnover intention. Digital capability has a positive effect on employee engagement, but its direct effect on turnover intention is not significant. Employee engagement was found to mediate the relationship between employer branding and turnover intention, as well as between digital capability and turnover intention. These findings reinforce the relevance of Social Exchange Theory and the Resource-Based View in the context of human resource management in the SME sector, while also providing practical implications that strengthening employer branding and enhancing employees' digital competencies can reduce turnover intention.